Penegakan Hukum terhadap Korporasi Pelaku Tindak Pidana Perdagangan Orang dari Perspektif Perlindungan Korban (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
The government's efforts to overcome the crime of human trafficking committed by corporations are stated in Article 13 of Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking. This study focuses on discussing the crime of human trafficking committed by corporations.The research method used is a normative legal approach. This study uses a statute approach and a case approach which in principle originates from primary legal materials consisting of laws and judges' decisions, secondary legal materials consisting of books, research results, articles and tertiary legal materials from libraries, articles and websites. The legal material analysis technique uses grammatical interpretation techniques.The results of this study show that law enforcement is closely related to criminal liability by corporations so that when a corporation is involved as a perpetrator of a crime, the corporate management can be held criminally responsible and legal protection for victims of human trafficking in this case is in the form of restitution or compensation, this is stated in Article 48 of Law Number 21 of 2007, but in its implementation, law enforcement does not pay attention to restitution for victims, this can be seen in the court decision in the verdict that there is no compensation for the victim's recovery. law enforcement, corporations, human trafficking crimes